Catholic and Muslim Human Rights Activism in Violent Internal Conflicts. Issue 1 (19th December 2014) - Tezcür, Güneş Murat
Abstract: When do religious organizations develop human rights platforms during violent internal conflicts? This article offers the first comparative study to address this question and focuses on religious organizations in El Salvador, Peru, Turkey, and Indonesia. It identifies two causal factors to explain variation in religious human rights activism in these four countries: (1) transnational religious ideas and linkages, and (2) the nature of the state-religion relationship. First, Vatican II and Liberation theology significantly contributed to the rise of religious human rights activism in El Salvador and Peru. Similar transitional linkages were absent in Turkey and Indonesia. Next, the more conflictual nature of the state-religion relationship in El Salvador explains why the Salvadorian Church pursued a more determined human rights agenda than its Peruvian counterpart. A similarly conflictual state-religion relationship contributed to the presence of Islamic human rights activism in Turkey, and a less conflictual relationship prevented its emergence in Indonesia.